Elimination of Fixed Checkin/Check-Out Time as a Source of Entrepreneurial Edge in Hotel Business - Uzonna Joseph, Onyemeh (2013)
This research uses the travails of a young engineer, Nigel, during his international travels and challenges he encountered with erratic check-in/checkout time at hotels, to explore the elimination of fixed check-in/check-out as an entrepreneurial opportunity that can generate competitive advantage. The hotel industry in Malaysia, a Southeast Asian country of about 28million people, provides the contextual background for the study. The situation analysis of Malaysia hotel industry was used to expound on the industry’s dynamics, strengths, opportunities, threats and weakness, with emphasis on the importance of tourism and its growth projections for Malaysia; the influence of government policies; import of increasing crime rate and shortage of labour; relevance of Malaysian’s natural resources and its strategic location in the region. The key concepts associated with the research objective are service quality and entrepreneurship; hence available literatures in these areas were reviewed as a foundation to establish the connection between the two. Discussion on service quality explored its link to profitability of a business; how it is measured and service recovery when unsatisfactory service encounter occurs. For the entrepreneurship part, existing literatures on entrepreneurial cognition and entrepreneurial orientation were used to explore how both contribute towards opportunity recognition and competitive advantage. Using questionnaire responses from 101 guests in Malaysian hotels and interview responses from six entrepreneurs in Malaysia hotel industry, the hypotheses derived from the main research questions were checked for fulfilment. Subsequently, four of the five hypotheses were seen as fully supported while one was only partially supported. The research concludes with the following findings: • Check-in/check-out time is an important aspect of hotel experience and a gap exists in fulfilling this need. Implementing a 24-hour boarding basis (by eliminating fixed check-in/check-out time) will fill this gap and lead to more patronage, while proving a source of competitive advantage. • Entrepreneurial orientation behaviours like innovativeness and alertness, lead to recognition of opportunities/new market space and entrepreneurial cognition is a key contributing factor.